Psychological Stress, Intestinal Barrier Dysfunctions, and Autoimmune Disorders: An Overview - Ilchmann-Diounou, Hanna; Menard, Sandrine (Frontiers in Immunology, 2020)
Autoimmune disorders (AD) are multifactorial diseases involving, genetic, epigenetic and environmental factors characterized by an inappropriate immune response toward self-antigens. In the past decades, there has been a continuous rise in the incidence of AD, which cannot be explained by genetic factors alone. Influence of psychological stress on the development or the course of autoimmune disorders has been discussed for a long time. Indeed, based on epidemiological studies, stress has been suggested to precede AD occurrence and to exacerbate symptoms. Furthermore, compiling data showed that most of AD are associated with gastro-intestinal symptoms i.e. microbiota dysbiosis, intestinal hyperpermeability and intestinal inflammation. Interestingly, social stress (acute or chronic, in adult or in neonate) is a well described intestinal disrupting factor. Taken together those observations questioned a potential role of stress-induced defect of intestinal barrier in the onset and/or the course of AD. In this review, we aim to present evidences supporting the hypothesis for a role of stress-induced intestinal barrier disruption in the onset and/or the course of AD. We will mainly focus on autoimmune Type 1 Diabetes, Multiple Sclerosis and Systemic Lupus Erythematous, AD for which we could find sufficient circumstantial data to support this hypothesis. We excluded gastrointestinal (GI) AD like coeliac disease to privilege AD not focused on intestinal disorders to avoid confounding factors. Indeed, GIAD are characterized by antibodies directed against intestinal barrier actors.